Nutritional Contributions to the Physical-Chemical and Biochemical Properties of Cassava (Manihot Esculenta Crantz) Leaves Grown in South Benin - Togbe, Finagnon Crepin Alexis; YETE, PELAGIE; YOVO, Franck; Wotto, Valentin (My University, 2020)
The objective of this study was to determine some physico-chemical and biochemical parameters of the leaves of a sweet variety of cassava (Manihot esculenta crantz) grown in South Benin, particularly in the regions of Pobè, Adja-ouèrè and Kétou, in order to assess their nutritional value. The results revealed that cassava leaves are a good source of fiber, the vitamin C content of the leaves varied from 69.48 to 75.16 mg/100 g of fresh matter; beta-carotene, varied from 1970 to 2347 μg/100 g of fresh matter. They were also rich in mineral elements with potassium values ranging from 18784 to 23542 mg/100 g of fresh matter. The calcium content varied from 1065 to 1260 mg / 100 g dry matter, and the phosphorus content varied from 1369 to 2410 mg / 100 g of dry matter. The magnesium content ranged from 1330 to 1680 mg / 100 g of dry matter. The iron content varied from 13 to 15 mg / 100 g of dry matter. The protein content was more than 30%. These leaves are good sources of carbohydrates with contents ranging from 160 to 170 mg / 100 g of dry matter for reducing sugars and 1340 to 1630 mg / 100 g of dry matter for total sugars. The analysis of these parameters revealed that cassava leaves are an important nutritional intake due to their high content of vitamin C and beta carotene, minerals, and soluble and insoluble fibers that have a beneficial effect on the intestinal mucosa. In view of these various benefits, it would be appropriate to encourage the population to consume cassava leaves because they have a very high nutritional value.
Keywords: Cassava leaves; chemical composition; nutritional value.